The influence of COVID-19 restrictions on bladder and bowel symptoms: A Case Report - Marie Nativ; Boaz Appel; Valentin Shabataev; Alexander Greenstein; Ilan Gruenwald (Archive of Urological Research - Peertechz Publications, 2021)
Background: The COVID-19 pandemic has undoubtedly affected millions around the globe. The infection and the restrictions applied to eradicate it carry with them physical and mental consequences related to stress and change of daily habits. In our case report, we describe the effect of COVID-19 lockdowns on urinary and bowel symptoms, as well as the mental health. Our patient was followed during a period of three lockdowns. Urinary and bowel symptoms as well as mental health were reported by a pelvic floor physiotherapist, using validated questionnaires, throughout lockdown and non-lockdown periods.  Results: Our results show that during lockdown periods, there is a transient decrease in patient's quality of life, which improved in the non-lockdown periods. Conclusion: COVID-19 restrictions alter patient's physical and mental health, indirectly related to the viral infection. Many patients may suffer from worsening urinary, bowel and mental symptoms that may need closer surveillance during lockdown periods. Healthcare workers should emphasize the importance of keeping a routine during lockdown periods and preventive measures should be taken in the form of home exercises instructions and phone follow up.